Development of moving object detection and tracking - Zainon, Muhammad Kamal Rizal (Universiti Teknologi PETRONAS, 2017)
Object detection is a process of locating and identifying the position of object in the frame of a video sequence. While object tracking is the process of locating the object of interest over time in the sequence of video frame. The steps of object detection and tracking is start with detection of object of interest, followed by tracking of the object over time and lastly the analysis of trajectory of tracked object. Object detection and tracking have been implemented mostly in the field of control, security and surveillance like vehicle navigation and human robot interaction. But, object detection and tracking is not perfect as problems still emerged such as dynamic background, for multiple objects and expensive computational hardware. This work explores the commonly used object detection and tracking technique. The suitable method for static camera was implemented in Matlab and OpenCV on a sample pedestrian video. In the end, the results of both software were shown.